The Role of Subject Teachers as Counselors in the Teaching Learning Process - Sutirna, Sutirna (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2019)
Teachers have three roles in carrying out their duties, namely the role of educators, instructors and mentors. The role as an educator is always required to be a role model in his steps both in the school environment and in the community, then the role as a teacher always provides knowledge in accordance with his field in a humanistic manner, while the role as a supervisor is to deliver students to be able to overcome their own problems with encouragement and attention to his personality. Misperception about the task of implementing guidance and counseling services in schools is only done by guidance and counseling teachers, it seems that there needs to be an improvement in the perception of subject teachers. Therefore, to change this, universities as prospective subject teacher printers must provide guidance and counseling courses with explanatory content leading to the role of subject teachers as supervisors.